Urinary biomarkers in assessing the nephrotoxic potential of gentamicin in solitary kidney patients after 7 days of therapy. (May 2014) - Gluhovschi, Gheorghe; Gadalean, Florica; Gluhovschi, Cristina; Velciov, Silvia; Petrica, Ligia; Bob, Flaviu; Bozdog, Gheorghe; Kaycsa, Adriana
Abstract Introduction: The solitary kidney (SK) may present increased vulnerability to nephrotoxicity because of adaptive phenomena. Aims: Assessing the vulnerability of the SK with urinary tract infections (UTI) to gentamicin by means of urinary biomarkers (N-acetyl-beta-D-glucosaminidase (NAG) and urinary alpha-1-microglobulin), as well as glomerular filtration rate (GFR). Methods: We studied 14 patients with SK with UTI (group A) (mean age 58.07 ± 13.61 years, mean duration of SK 13.55 ± 12.33 years) who were administered gentamicin for 7 days. Group B consisted by 17 patients with SK without any other associated renal pathology (average age 51.17 ± 9.39 years, average existence period of a single kidney 33.23 ± 21.73 years). We also included a third group (group C) represented by nine healthy individuals, with two kidneys. Results: Increased values of urinary NAG were found in group B as compared to group C and alpha-1 microglobulin in group A as compared to group B. During treatment with gentamicin, increased values of both NAG and alpha-1-microglobulin in group A were found on day 7 as compared to values before treatment (day 7 NAG = 18.99 ± 14.07 U/g creat versus day 0, NAG = 5.15 ± 6.54 U/g creat, p = 0.004; day 7 alpha-1-microglobulin = 20.88 ± 18.84 mg/g creat versus day 0, urinary alpha-1-microglobulin = 4.96 ± 6.57 mg/g creat, p = 0.003). No statistically significant alterations of GFR were noticed after 7 days of treatment. Conclusions: We found the nephrotoxic effects of gentamicin at tubular level, but not at glomerular level. The nephrotoxic potential of gentamicin in patients with a SK can be monitored by assessing urinary biomarkers during treatment of UTI.